Community Service for Providing Additional Food for Tempeh Pudding (PUTSAL) in Posyandu Aster Mekarjaya Village, Tarogong Kaler Garut District - Dewi Viani; Azzahroh, Putri; Wili Oktavianti; Ani Maryani; Siti Nurfauji Islami; Kasim, Yeni Rachman; Nia Kurniatin (International Journal of Community Services, 2025)
Background: The latest SSGI data in 2022 shows a stunting rate of 21.6%. This figure is still very high considering that the target for reducing stunting in 2024 is 14%. In other cases of malnutrition, namely wasting in children, has increased compared to 2021, namely 7.1% to 7.7%. (JPGI, 2023) Based on a preliminary survey on maternal and child health in Mekarjaya Village based on the 2023 Mekarwangi Health Center report, the number of children under five was 367 and as many as 128 (34.87%) toddlers experienced malnutrition problems, including stunting 63 (17.6%), wasting 16 (0.4%) and under weight 49 (13.3%). The impact of malnutrition on children will affect firstly a decrease in the child's immunity so that the child is easily sick and affected by infections, secondly a delay in growth and development, third, physical growth will be disturbed, fourth, brain development is disturbed, children have problems in emotional and behavioral turmoil and the sixth is susceptible to chronic diseases. This impact will certainly affect the quality of children's lives and will affect the quality of the nation's next generation. (Ministry of Health of the Republic of Indonesia 2023). This impact will certainly affect the quality of children's lives and will affect the quality of the nation's next generation. (Ministry of Health of the Republic of Indonesia 2023). Efforts to handle malnutrition are by providing solid foods that have a high calorie and protein content. From the results of the study, it is said that 100 gr tempeh pudding has a total energy content of 51.65 kcal compared to the pudding standard from BPOM, which is 20-40 kcal/100 gr. Tempeh pudding has a higher protein than regular pudding because the protein content is 2.80 because it contains milk as an animal protein and tempeh as a vegetable protein and so the total energy content increases. (Widiastuti, 2024) Objective: This community service aims to empower the community by increasing the knowledge of mothers under five about the impact of malnutrition and handling of malnutrition in toddlers. Methods: The method used in community service is by providing counseling on the impact of malnutrition on toddlers and the introduction of the "PUTSAL" innovation as a food innovation with a high calorie and protein content. Conclusion: Based on the results of the evaluation after being given counseling and providing innovative products "Putsal", it can be concluded that there is an increase in participants' knowledge as seen from participants who are able to answer questions about the impact that occurs on toddlers with malnutrition and how to overcome it.